2018
DOI: 10.1111/crj.12752
|View full text |Cite
|
Sign up to set email alerts
|

Blood biomarkers as predictors of long‐term mortality in COPD

Abstract: High CRP and neutrophils as well as low eosinophils are predictive of poor COPD prognosis. They also add significant value to prediction models of mortality in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
3
33
0
1
Order By: Relevance
“…In the current study, CRP did not differ significantly between the seasons and was not correlated with serum 25(OH)D concentration at either time point, a finding that confirms the findings of others 52. Although higher concentrations of CRP have been associated with impaired lung function, the role of CRP in the etiology of COPD and respiratory function remains poorly understood 56,57. Further research is also warranted to elucidate the relationship between vitamin D and immune-respiratory function in COPD.…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, CRP did not differ significantly between the seasons and was not correlated with serum 25(OH)D concentration at either time point, a finding that confirms the findings of others 52. Although higher concentrations of CRP have been associated with impaired lung function, the role of CRP in the etiology of COPD and respiratory function remains poorly understood 56,57. Further research is also warranted to elucidate the relationship between vitamin D and immune-respiratory function in COPD.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that CRP could be used as an independent in uencing factor to evaluate the control level of COPD chronic in ammation in patients, [12][13][14] while ALB is a prognostic marker of infection-related disease. 15 Our study observed that high CRP and PCT levels as well as low ALB level were associated with death in AECOPD patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis in COPD patients showed that CRP elevation is especially significant in late mortality (11). High CRP and neutrophil levels, as well as low eosinophil levels have been shown to be poor prognostic factors (12).…”
Section: Discussionmentioning
confidence: 99%